Size and nature of the Auckland private rented sector – Implications for the spread of housing options - Egbelakin, TK; Kim, G; Rasheed, E (Tampere University of Technology, 2016)
Housing scarcity and unaffordability in recent years has been a major concern in New Zealand’s major cities, especially in Auckland. The need to accommodate New Zealand’s growing population is a concern that is central to government housing policy, with attention having recently been focused on the capacity of the private rental sector to meet a range of housing needs. The objective of this research was to investigate the size and nature of the private rental housing sector in the Auckland region and to examine how the sector contributes to the spread of housing options in the region. Through the analysis of the existing data from five consecutive censuses, the research findings present a detailed analysis of the Auckland private rented sector, with a particular emphasis on the types of household it accommodates, their location within the region and the main housing typologies. These findings will assist various organisations and public authorities to establish priorities in their housing strategies in a way that best meets the demands of the current market, and also to clarify issues around the efficacy of existing policies relating to private renting.
Keywords: Housing; Private Rented Sector (PRS); Auckland; New Zealand